On electrogenerated acid-facilitated electrografting of aryltriazenes to create well-defined aryl-tethered films - Vinther, Jesper (Langmuir : the ACS journal of surfaces and colloids, 2013)
The mechanism of electrogenerated acid-facilitated electrografting (EGAFE) of the aryltriazene, 4-(3,3-dimethyltriaz-1-enyl)benzyl-1-ferrocene carboxylate, was studied in detail using electrochemical quartz crystal microbalance (EQCM) and cyclic voltammetry. The measurements support the previously suggested mechanism that electrochemical oxidation of the EGA agent (i.e., N,N'-diphenylhydrazine) occurs on the forward oxidative sweep to generate protons, which in turn protonate the aryltriazene to form the corresponding aryldiazonium salt close to the electrode surface. On the reverse sweep, the electrochemical reduction of the aryldiazonium salt takes place, resulting in the electrografting of aryl groups. The EGAFE-generated film consists of a densely packed layer of ferrocenyl groups with nearly ideal electrochemical properties. The uncharged grafted film contains no solvent and electrolyte, but counterions and solvent can easily enter and be accommodated in the film upon charging. It is shown that all ferrocene moieties present in the multilayered film are electrochemically active, suggesting that the carbon skeleton possesses a sufficiently high flexibility to allow the occurrence of fast electron transfers between the randomly located redox stations. In comparison, EQCM measurements on aryldiazonium-grafted films reveal that they have a substantially smaller electrolyte uptake during charging and that they contain only 50% electroactive ferrocenyl groups relative to weight. Hence, half of these films consist of entrapped supporting electrolyte/solvent and/or simply electrochemically inactive material due to solvent inaccessibility